1985
DOI: 10.2307/2937371
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Stream Drift Mechanisms: An Experimental and Observational Approach

Abstract: Laboratory experiments were conducted with the periphyton—grazing mayfly Baetis tricaudatus to test the hypothesis that stream drift results from the passive removal of individuals from substrates. This hypothesis accounts for entry into the water column and diel drift periodicities, based on changes in the positioning of individuals on substrates and changes in their activity rates. A factorial design that incorporated food abundance (low or high), food distribution (low, intermediate, or high degree of patch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(126 citation statements)
references
References 35 publications
6
118
0
1
Order By: Relevance
“…Active drift, in contrast, results from deliberate behaviours, including benthic predator avoidance (Peckarsky 1980;Malmqvist and Sjostrom 1987;Kratz 1996;Huhta et al 2000), active patch selection while foraging (Hildebrand 1974;Kohler 1985), or escape from unfavourable abiotic conditions (Lauridsen and Friberg 2005;Gibbins et al 2007b;James et al 2009;Larsen and Ormerod 2010). Density dependence may also increase drift entry owing to increased competition for space (Corkum 1978;Hildrew and Townsend 1980;Kohler 1992) or resource limitation (Dimond 1967;Richardson 1991;Fonseca and Hart 1996;Rowe and Richardson 2001;Siler et al 2001).…”
Section: Drift Entrymentioning
confidence: 99%
“…Active drift, in contrast, results from deliberate behaviours, including benthic predator avoidance (Peckarsky 1980;Malmqvist and Sjostrom 1987;Kratz 1996;Huhta et al 2000), active patch selection while foraging (Hildebrand 1974;Kohler 1985), or escape from unfavourable abiotic conditions (Lauridsen and Friberg 2005;Gibbins et al 2007b;James et al 2009;Larsen and Ormerod 2010). Density dependence may also increase drift entry owing to increased competition for space (Corkum 1978;Hildrew and Townsend 1980;Kohler 1992) or resource limitation (Dimond 1967;Richardson 1991;Fonseca and Hart 1996;Rowe and Richardson 2001;Siler et al 2001).…”
Section: Drift Entrymentioning
confidence: 99%
“…The specific mechanisms explaining the pattern consistent with post-recruitment densitydependent losses of these mayflies in both types of streams are unresolved, but potentially include dispersal or mortality caused by predation, crowding, food limitation or competition for space, as have been demonstrated in other systems (Kohler 1985, Forrester 1990, Morse 1993, Fonseca and Hart 1996, Wilson and Osenberg 2002. While mermithid parasites have been reported to cause mortality in early instar B. bicaudatus, rates of infection did not increase with population density (Vance and Peckarsky 1996).…”
Section: Discussionmentioning
confidence: 87%
“…Initial population sizes are established when eggs are oviposited in streams by winged adult females (Elliott and Humpesch 1980). Subsequently, larvae drift downstream in search of food (Kohler 1985), via fluid mediated dispersal (Fonseca 1999) often to avoid predation (Peckarsky 1996).…”
Section: Introductionmentioning
confidence: 99%
“…He found that only after the benthos reached a "recovered" density (compared to pre-insecticide levels) did drift become significant. Others, too, have suggested that drift may be a densitydependent mechanism of the benthos (Kohler 1985, Anholt 1995, Turner and Williams 2000.…”
mentioning
confidence: 99%